Ama...Ina...Anak - Reyes, Jose Javier; Soriano, Maricel; Manzano, Edu. (Quezon City Star Cinema Production, 2001)
A touching film which discusses the issue on adoption. A film which everyone can relate to wheter you are a mother, father or child.
DVD
Maricel Soriano, Edu Manzano.